Study of Doppler broadening Compton scattering and cross section determination for the elements Fe, Zn, Ag, Au and Hg - Abood, Wrood K. (Iraqi Journal of Physics, 2019)
To assess the contribution of Doppler broadening and examine the Compton profile, the Compton energy absorption cross sections are measured and calculated using formulas based on a relativistic impulse approximation. The Compton energy-absorption cross sections are evaluated for different elements (Fe, Zn, Ag, Au and Hg) and for a photon energy range (1 - 100 keV). With using these crosssections, the Compton component of the mass–energy absorption coefficient was derived, where the electron momentum prior to the scattering event caused a Doppler broadening of the Compton line. Also, the momentum resolution function was evaluated in terms of incident and scattered photon energy and scattering angle. The results of cross sections for the coherent and incoherent processes are compared with theoretical values and reported values of other researchers. The present results are in agreement with the theoretical values.